Node selection algorithm based on channel coefficient for cognitive network - Jin-huai GUO; Ke-feng FAN; Su-bing ZHANG (Tongxin xuebao)
To improve communication performance of cognitive network,according to the principle of opportunity cooperative communication,node selection algorithm based on channel coefficient for cognitive network was proposed and studied.Results show that the proposed algorithm can enhance spectrum utilize efficiency and improve network throughput effectively.